PENATALAKSANAAN FISIOTERAPI PADA KASUS BELL’S PALSY SINISTRA DENGAN MODALITAS INFRA RED, ELECTRICAL STIMULATION (FARADIK) DAN MASSAGE DI RSUD CILILIN - Sania Indah Pratiwi; Karlina Karlina; Ika Rahman (LPPM Sekolah Tinggi Ilmu Kesehatan Siti Hajar Medan, 2021)
Introduction. Bell's Palsy is paralysis of the peripheral nervus VII (Facialis) that arises acutely in the absence of other neurologic abnormalities and the cause is unknown. Objective: To determine the management of physiotherapy in increasing facial muscle strength and increasing the functional ability of facial muscles in Bell's Palsy sufferers with InfraRed, Electrical Stimulation and Massage modalities. Results: After doing therapy for 6 times, it was found that there was an increase in facial muscle function from the resting/silent position T1:10 to T6:14, frowning T1:3 to T6:10, closing the eyes T1:9 to T6:21, smiling T1:15 to T6:21, and whistling/washing T1:3 to T6:7. The increase in facial muscle strength was the result of M. Frontalis T1:1 to T6:5, M. Orbicularis Occuli T1:1 to T6:3, M.Zygomaticus Major T1:1 to T6:3, M. Orbicularis Oris T1:1 to T6:3, M. Procerus T1:0 to T6:3, M. Bucinator T1:1 to T6:5, M. Depressor Anguli Oris, T1:0 to T6:3 M. Corrugator Supercillii T1:1 to T6: 3, M. Nasalis T1:0 becomes T6:3, M. Inferior Labi Depressor T1:1 becomes T6:3, M. Mentalis T1:1 becomes T6:3, on M. Platysma T1:1 becomes T6:5. Conclusion: The use of InfraRed, Electrical Stimulation and Massage is effective in improving facial muscle function and facial muscle strength